Effects of Salinity on the Growth, Survival and Proximate Composition of Pangas, Pangasius Hypophthalmus (Bangladesh Journal of Zoology, 2020)
Climate change induced salinity intrusion has a global and local effect on the aquaculture production. Thai-Pangas (Pangasius hypophthalmus) has become one of the cheapest protein sources in Bangladesh because of its wide range of environment tolerance, excellent growth and survival rate. Present study was thus conducted to measure the effects of salinity on the growth performance and survival of pangas. For the determination of the effect of salinity on growth and survival, 15-day old fingerlings were reared in 0, 2, 4, 6, 8, 10, 12, 14 and 20‰ for 60 day at laboratory condition. All fish fingerlings in treatment with 20‰ salinity died within 6 hours of stocking while 62.5% mortality was found within 6 hours at 14‰ salinity. No mortality was detected in other treatment groups. Significantly higher specific growth rate was detected at 0, 2 and 4‰ salinity than that of 12 and 14‰ salinity. No significant change in food conversation ratio was found among treatments. No significant difference was observed on proximate composition between and within treatments. Water quality parameters include temperature, dissolved oxygen and pH were 27.23 ± 0.02 °C, 8.33 ± 0.05 mg/L and 8.05 ± 0.03, respectively throughout the experimental period. Thus, the present study suggests the suitability of pangas fingerlings at up to 4‰ saline water with desirable growth rate.Bangladesh J. Zool. 48(1): 141-149, 2020